INTERPRETATION OF ANGER VERSES IN TAFSIR AL-JAYLANI - Abdillah, Abdillah; Gama, Cipta Bakti (Ma'had Aly As'adiyah Sengkang, 2024)
This study examines the concept of anger in the Qur'an based on key vocabulary. Anger is discussed in the context of God, the Prophet, and disbelievers, with various positive and negative meanings. The research aims to classify verses about anger and analyze their meanings according to Tafsīr al-Jaylānī. Using a qualitative method and thematic approach (mauḍū'i), this research examines the thoughts of 'Abd al-Qādir Jaylānī. The results show 45 verses discussing anger, with four key terms: gaḍab (anger affecting verbal expression and physical action), makẓūm (anger accompanied by grudge), gayẓ (explosive anger that damages the heart), and sukhṭ (anger due to inappropriate actions). This research provides insights into various aspects of anger in the Qur'an and its interpretation in Tafsīr al-Jaylānī.